2014
DOI: 10.1016/j.optlaseng.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Fibre laser piercing of mild steel – The effects of power intensity, gas type and pressure

Abstract: Laser piercing is used to generate a starting point for laser cutting. The pierced hole is normally larger than the kerf width, which means that it cannot lie on the cut line. An experimental program investigating the piercing process as a function of laser and assist gas parameters is presented. An Nd:YAG fibre laser with a maximum power of 2 kW was used in continuous wave mode to pierce holes in 2 mm thick mild steel. Oxygen and nitrogen were used as assist gases, with pressures ranging from 0.3 to 12 bar. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Piercing and laser cutting are two independent processes in which material evacuation have different mechanisms [1,2]. In the piercing, the laser beam is stationary with respect to the workpiece and the melt material is ejected upwards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piercing and laser cutting are two independent processes in which material evacuation have different mechanisms [1,2]. In the piercing, the laser beam is stationary with respect to the workpiece and the melt material is ejected upwards.…”
Section: Introductionmentioning
confidence: 99%
“…The authors developed a new piercing technique known as PRPM (power ramped pulsed mode) obtaining smaller piercing holes with greater circularity and less ejected material than in normal pulse mode. In mild steel, researchers [2,11] observed that increasing the power of the peak or the duty cycle, increased the size of the hole and the irregularity of its shape and ejected material, also obtaining wider piercings with oxygen assist gas than with nitrogen. Pocorni et al [12] investigated the piercing process in the laser cutting of stainless steel, demonstrating that appropriate laser power modulation settings could considerably reduce both the piercing time and the required energy to generate the piercing hole, also affecting its size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation